EFEKTIVITAS KOMPETENSI DASAR UBUDIYAH (KDU) TERHADAP PEMBENTUKAN MENTAL DAN KARAKTER PESERTA DIDIK : THE EFFECTIVENESS OF BASIC COMPETENCIES OF UBUDIYAH (KDU) ON THE MENTAL AND CHARACTER FORMATION OF STUDENTS - Maruf, Abdullah; Jumaidi; Amirotunniswah (CV. Kalimasada Group, 2023)
The current Indonesian education system is changing to a more holistic approach that prioritizes the mental and character development of students in addition to academic success. Basic Competency Program (KDU) Ubudiyah is an effort that seeks to instill core values and principles of Islam to students. The purpose of this study was to determine how well the program shapes the character and mental development of Class 12 MA Raudlatut Tholibin Pakistan students. This study aims to: (1) Describe the implementation of the KDU program in MA Raudlatut Tholibin Pakis; (2) assess the influence of the program on the character and mental development of students; and (3) determine the factors that facilitate and inhibit the implementation of the program. Observation, interviews, and documentation are some of the data collection methods used in this qualitative research. Qualitative descriptive method is used to analyze the data. As shown by the professionalism of the KDU examiners and the fact that 90% of the facilities and infrastructure needed are suitable, the results show that the implementation of the KDU program at MA Raudlatut Tholibin Pakis can be considered effective. At MA Raudlatut Tholibin Fern, a qualitative review of the program's effects on Grade 12 students revealed that it greatly improved their character and mental development